2012
DOI: 10.1055/s-0031-1299746
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution Study of Naringin in Rats by Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Naringin (CAS 10236-47-2), a flavanone glucoside widely present in fruits of citrus plants, has received extensive studies on its potential effects on health benefits and was recently demonstrated to be a putative antitussive. In this study, we determined the tissue distributions of naringin and its metabolites (naringenin and naringenin's conjugates) in rats to examine whether they undergo selective uptake by specific organs. Naringin was administered orally to rats at the dose of 42 mg/kg and the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
3
26
1
Order By: Relevance
“…Among assayed organs, the liver contained higher naringenin sulfate and naringenin glucuronide concentrations than other organs, which concurred with previous studies [ 19 ] and indicated these naringenin conjugates have higher protein binding with liver proteins. In the liver, concentration of naringenin sulfates was higher than that of naringenin glucuronides by 240%.…”
Section: Discussionsupporting
confidence: 91%
“…Among assayed organs, the liver contained higher naringenin sulfate and naringenin glucuronide concentrations than other organs, which concurred with previous studies [ 19 ] and indicated these naringenin conjugates have higher protein binding with liver proteins. In the liver, concentration of naringenin sulfates was higher than that of naringenin glucuronides by 240%.…”
Section: Discussionsupporting
confidence: 91%
“…In pharmacokinetic studies, naringin was administered orally to rats at a dose of 42 mg/kg, which was converted from 36.8 mg/kg in guinea pigs [23,24]. Thus, the middle dose (18.4 mg/kg) was chosen in the present study based on pharmacodynamic and pharmacokinetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…into mice chronically treated with D-galactose lessens their cognitive impairment and mitochondrial dysfunction [22]; and (6) the administration of NGIN (100 mg/kg/day for 16 weeks) to Alzheimer's disease-model mice (APPswe/PS1dE9) improves long-term memory [23]. As NGIN and its metabolites have been shown to have difficulty in crossing the blood-brain barrier (BBB) [24], the BBB might have been destroyed in these cases, consequently permitting NGIN (and probably NRTN) to exert a potent antioxidative effect on the brain.…”
Section: Discussionmentioning
confidence: 99%